Analysis of differential expression profile of miRNA in peripheral blood of patients with lung cancer. Issue 9 (20th September 2019) - He, Qingfang; Fang, Yirong; Lu, Feng; Pan, Jin; Wang, Lixin; Gong, Weiwei; Fei, Fangrong; Cui, Jingjie; Zhong, Jieming; Hu, Ruying; Liang, Mingbin; Fang, Le; et al.
Abstract: Purpose: To identify potential molecular targets for lung cancer intervention and diagnosis, we analyzed the differential miRNA expression of peripheral blood between lung cancer patients and healthy controls. Methods: Three pairs of cases' and controls' peripheral blood samples were evaluated for miRNA expression by microarray. 12 miRNAs were selected for RT‐PCR validation and target genes prediction. In addition, 4 miRNAs were selected for future validation by RT‐PCR in a large sample of 145 cases and 55 frequency‐matched healthy controls. Results: A total of 338 differentially expressed miRNAs were screened and identified by microarray. According to the fold changes, the top ten upregulated miRNAs were hsa‐miR‐124‐3p, hsa‐miR‐379‐5p, hsa‐miR‐3655, hsa‐miR‐450b‐5p, hsa‐miR‐29a‐5p, hsa‐miR‐200a‐3p, hsa‐miR‐542‐3p, hsa‐miR‐138‐5p, hsa‐miR‐219a‐2‐3p, and hsa‐miR‐4701‐3p, and the top ten downregulated miRNAs were hsa‐miR‐34c‐5p, hsa‐miR‐135a‐5p, hsa‐miR‐132‐3p, hsa‐miR‐3178, hsa‐miR‐4449, hsa‐miR‐4999‐3p, hsa‐miR‐1246, hsa‐miR‐4424, hsa‐miR‐1252‐5p, and hsa‐miR‐24‐2‐5p. RT‐PCR verification of the 12 miRNAs revealed that 5 of 8 upregulated miRNAs, 2 of 4 downregulated miRNAs showed a significant difference between the cases and controls ( P < .05). A large number of target genes and their functional set showed overlapping among the 453 predicted target genes of the 12 miRNAs ( P < .01). RT‐PCR in the large sample confirmed the significant differential expression level of hsa‐miR‐29a‐5p, hsa‐miR‐135a‐5p, hsa‐miR‐542‐3p, and hsa‐miR‐4491 between cases and controls ( P < .05), and three of these microRNA, except hsa‐miR‐29a‐5p, were significant after Bonferroni correction for adjustment of multiple comparisons. Conclusion: There was a significant difference in miRNAs expression in the peripheral blood between lung cancer patients and healthy controls, and 4 miRNAs were validated by a large‐size sample.